Post-War Regimes and State Reconstruction in Liberia and Sierra Leone - Sesay, Amadu (Book collections on Project MUSE., 2009)
The shocks of the unexpected outbreak of violent internal armed conflicts in post Cold War West Africa continue to linger in policy and academic circles. While considerable attention is devoted to explaining the civil wars, there is little understanding of the delicate and unpredictable processes of reconstruction. Post-war reconstruction programmes in Africa have become, by and large, externally driven processes; and while externalisation may not be negative per se, it is important to interrogate how such intervention recognises and interacts with local dynamics, and how it manipulates and conditions the outcomes of post-conflict reconstruction agenda.